2022
DOI: 10.2991/aebmr.k.220104.033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Capital Adequacy, Market Risk, Credit Risk, Operational Risk and Liquidity on the Profitability (Case Study on Sharia Banks Registered in OJK Period 2010-2019)

Abstract: Banking is a financial institution that has a role in the financial system in Indonesia. The existence of the banking sector becomes important because in carrying out life in the community involves services from the banking sector. Banking is an institution that has a strategic role as a financial intermediary (financial intermediary) between parties who have funds (surplus funds) with parties who need funds (deficit funds), as well as institutions that function to facilitate payment-traffic. The Islamic banki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Thus, NPLs will have a negative effect on bank performance. (Siddique, Khan, & Khan, 2022), (Y. S. Sari, Ardiansari, & Widia, 2022) and (Huong, Nga, & Oanh, 2021) found a significant and…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Thus, NPLs will have a negative effect on bank performance. (Siddique, Khan, & Khan, 2022), (Y. S. Sari, Ardiansari, & Widia, 2022) and (Huong, Nga, & Oanh, 2021) found a significant and…”
Section: Introductionmentioning
confidence: 90%
“…If the capital is large enough, it can also be used to increase the credit distributed, thereby increasing profitability (Thoa, Anh, & Minh, 2020). Siddique et al, (2022); Ikpesu & Oke., (2022) and Mir & Shah., (2022) found that CAR had a positive effect on profitability, while Sari et al, (2022) and (Sahyouni & Wang, 2019) actually found that CAR had no effect on profitability.…”
Section: Ijfbs Vol 12 No 3 Issn: 2147-4486mentioning
confidence: 99%
See 1 more Smart Citation